COMPRESSIVE STRENGTH AND MODULUS OF ELASTICITY OF STEEL FIBER REINFORCED CONCRETE (SFRC) UNDER DIFFERENT TEMPERATURE CONDITIONS - Akesh, Sami Saleem; Sambowo, Kusno Adi; As’ad, Sholihin (Jurnal Teknik Sipil, 2014)
AbstractSFRC consists of concrete matrix with steel fibers that serve as reinforcement, which is useful to reduce the brittle nature of concrete. The use of steel fibers in this study aimed to determine the effect of steel fibers in the concrete compressive strength and modulus of elasticity. Temperature can affect properties of concrete, then in addition to determine the effect of steel fiber will do heat treatment at a certain temperature.This research was experimental methods and used cylindrical specimen with a diameter of 15 cm and a high of 30 cm. Specimens were 75 samples. Samples were SFRC containing fibers of 0%, 0.75% and 1:25%. Some samples were exposed in various temperature, ambient temperature, 200?C, 400?C, 600?C and 800?C. Compressive strength and modulus of elasticity were tested at 28 days and soon after elevated temperature exposed on samples.The test result that the compressive strength of concrete with steel fiber addition decreased compared to plain concrete. The modulus elasticity of samples increases with the amount of steel fibers in the concrete mix. The SFRC 0%, 0.75% and 1:25% compressive strength values are 39.066 MPa, 28.875 MPa and 31.705 MPa respectively while the modulus of elasticity 6322.353 MPa, 7697.876 MPa and 8873.661 Mpa respectively. After the temperature treatment of the specimen, the results of which are shown in the increasing temperature of the concrete, the compressive strength and modulus of elasticity decreased significantly. The highest compressive strength at temperatures of 800?C, shown in plain copkncrete with a value of 16,419 MPa, whereas elastic modulus obtained in 1:25% SFRC with a value of 2015,357 Mpa.Keywords: SFRC, Steel fiber, temperature, compressive strength. Modulus elasticity